Ethical concerns in utilising genetic engineering to alter the genetic make-up of foetuses / Nurhafizah Kamaruddin…[et al.] - Kamaruddin, Nurhafizah; Ahmed Bazari, Mohd Shafiq; Mokhsein, Maizura; Mohammad, Ain Aissa (2011)
The development of advanced technology has perpetuated the use of designer babies across the globe with a plethora of nations adopting different legal standings in the legislation of its use. The call for regulations, whether to permit or restrict this form of genetic engineering, has penetrated the state of Malaysia as well. Malaysian lawmakers have expressed their intention to ban designer babies in 2004 but the ethical, moral, social and legal reasons underlying this legal intention is lesser known. By analyzing the operations and nature of the science behind designer babies through case studies, correspondence with field experts and reviewing existing literature and laws; this research stands to reveal all of those related concerns. Furthermore, comparative analysis between these distinct legal standings allows this research to attribute which concerns are prioritized in the rational calculus of other governments. Findings of this research would allow Malaysia to draw parallels in concluding what is the most apt legal standing that reflects the Malaysian society. Thereby, reconciling what is Malaysia's current view with what this research deems as the optimum view for Malaysia to adopt. Application of all the relevant issues to the Malaysian context has subsequently equipped this paper to conclude with the recommendation of legalizing designer babies only in the circumstance where the non-intervention threatens the life of the future child.